Successful treatment with tislelizumab plus chemotherapy for SMARCA4-deficient undifferentiated tumor: a case report - Dong, Wen; Dai, Anli; Wu, Zhijun; Wang, Jiangtao; Wu, Tao; Du, Yangfeng; Tian, Wei; Zheng, Jiang; Zhang, Yan; Wang, Hongming; Cai, Juan; Dong, Susu; et al. (Frontiers in Immunology, 2024)
SMARCA4-deficient undifferentiated tumor (SMARCA4-dUT) is a devastating subtype of thoracic tumor with SMARCA4 inactivation and is characterized by rapid progression, poor prognosis, and high risk of postoperative recurrence. However, effective treatments for SMARCA4-dUT are lacking. Herein, we describe a patient with SMARCA4-dUT who exhibited an impressive response to the anti-programmed cell death protein-1 (PD-1) antibody (tislelizumab) in combination with conventional chemotherapy (etoposide and cisplatin). To the best of our knowledge, this is the first case of SMARCA4-dUT treated with chemotherapy, comprising etoposide and cisplatin, combined with anti-PD-1 inhibitors. Immunotherapy combined with etoposide and cisplatin may be a promising strategy to treat SMARCA4-dUT.